2013
DOI: 10.1016/j.ijid.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of a commonly used Zimbabwean herbal treatment (African potato) does not alter the pharmacokinetics of lopinavir/ritonavir

Abstract: Summary Objective African potato (Hypoxis obtusa) is commonly used in Sub-Saharan Africa as a complementary herbal remedy for HIV-infected patients. It is unknown whether or not co-administration of African potato alters the pharmacokinetics of protease inhibitor antiretrovirals. The objective of this study was to investigate the impact of the African potato on the steady-state pharmacokinetics of ritonavir-boosted lopinavir (LPV/r). Methods Sixteen adult volunteers were administered LPV/r 400/100 mg twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The supplements evaluated in these studies included African potato ( Hypoxis hemerocallidea or H. obtusa ), beta-carotene, Echinacea, fish oil, ginseng, goldenseal root, and Panax ginseng . 1618, 2123,25,26,28,29,30,32,33,3538…”
Section: Resultsmentioning
confidence: 99%
“…The supplements evaluated in these studies included African potato ( Hypoxis hemerocallidea or H. obtusa ), beta-carotene, Echinacea, fish oil, ginseng, goldenseal root, and Panax ginseng . 1618, 2123,25,26,28,29,30,32,33,3538…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3]6,11,[19][20][21][22] Since TDM is growing in popularity for all antiretroviral drugs, the premise of the study described here was that a lopinavir trough concentration value could predict the AUC in patients receiving a twice-daily regimen commonly used in practice. Because many of the pharmacokinetic studies also reported peak lopinavir concentrations, it was thought that peakdriven models for predicting the AUC could also be useful.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on ritonavir was not analyzed in this study. Total cholesterol and triglycerides were elevated but within limits during LPV/r treatment [18]. The investigators concluded that African Potato had no significant effect on the steady-state pharmacokinetics of LPV.…”
Section: Drug Interaction Studiesmentioning
confidence: 97%
“…[19] AUC area under the concentration-time curve within a dosing interval, BPH benign prostatic hyperplasia, BSS β-sitosterol, BSSG β-sitosterol glucoside, C max maximum concentration following dose administration, C trough plasma concentration at the end of the dosing interval, CL F apparent clearance, IPSS International Prostate Symptom Score, K el elimination rate constant, LPV/r ritonavir-boosted lopinavir, PTB pulmonary tuberculosis, T max time to reach C max , T 1/2half-life day was found to be therapeutic [19]. According to literature, an oral dose of 15 mg/ kg/ day is reportedly therapeutic [18]; however, it is unknown whether this dose is effective for all the claims against African Potato. Other sources state that 2400 mg taken daily is therapeutic [15].…”
Section: Dosage Recommendationsmentioning
confidence: 99%